Model Partisipasi Masyarakat Dalam Pengelolaan Badan Usaha Milik Desa (BUMDes) Di Desa Dadapan Kecamatan Pringkuku Kabupaten Pacitan - Nafida Arumdani; Arimurti Kriswibowo (Universitas Mataram, 2022)
One of the government's strategies in increasing local revenue is the issuance of the Minister of Village, Disadvantaged Regions and Transmigration Regulation Number 4 of 2015 concerning the Establishment, Management and Management, and Dissolution of Village-Owned Enterprises (BUMDes) which states that village governments can establish BUMDes. BUMDes is one of the parties that has a role to empower local potential to improve the welfare and economy of rural communities. The importance of BUMDes in driving the economy of rural communities shows that participatory management will have a positive effect on improving welfare. BUMDes cannot run alone without the participation of the government and support from the village community. The purpose of this study was to determine the model of community participation in the management of BUMDes in Dadapan Village, Pringkuku District, Pacitan Regency. The method used was descriptive qualitative research. The results of this study are that the Tugu Kuning BUMDes administrators have good organizational abilities, skills and experience as well as a high sense of attachment and commitment in developing their BUMDes supported by the Dadapan Village Government by providing full facilities for existing programs in BUMDes.